Offical methods of analysis of the Association of official analytical chemists (Association Offical Analytical Chemists, 1984)
There are the new teachniques appearing in this edition are inductively coupled plasma emission spectroscopy for simultaneous multielement determinations, and hydrophobic grid membrane filter methods for enumeration of coliforms in foods.